IMPLEMENTASI PERATURAN DAERAH PROVINSI SUMATERA BARAT NO 6 TAHUN 2014 TENTANG PENGUATAN LEMBAGA ADAT DAN PELESTARIAN NILAI BUDAYA MINANGKABAU - Fadri Ramadian; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
West Sumatra Province Regional Regulation No. 6 of 2014 concerning Strengthening of Customary Institutions and the Conservation of Minangkabau Cultural Values was made to improve the HR of customary stakeholders, enhancing the role of traditional institutions in preserving Minangkabau cultural values, so that Minangkabau cultural values are protected and preserved. The purpose of this study was to determine how the implementation of the Regional Regulation of West Sumatra Province No. 6 of 2014 Regarding the Strengthening of Customary Institutions and the Conservation of Minangkabau Cultural Values. And what are the inhibiting factors for the implementation of the Regional Regulation of the Province of West Sumatra No. 6 of 2014 concerning the Strengthening of Customary Institutions and the Preservation of Minangkabau Cultural Values. This research starts from the theory of public policy implementation approach from Donald Van Metter Carl Van Horn. The research method used is descriptive method with a qualitative approach. The results showed that the Implementation of the Regional Regulation of the Province of West Sumatra No. 6 of 2014 Regarding Strengthening Customary Institutions and the Conservation of Minangkabau Cultural Values has not been running optimally, because there are still problems regarding the strengthening of adat institutions. Failure to guide the organization and guidance of HR for customary institutions. Suggestion: Implementors increase the attitude of commitment and consistency in the implementation of a policy so that the policy is implemented optimally and the policy objectives are achieved. Keywords: Implementation, Regional Regulations, Customary Institutions, Culture